MORINGA LEAVES IMPROVE HYSTOPATOLOGY WHITE RATS HEPAR EXPERIENCED DIABETIC - Pidada, Ida Ayu Adhistania; Setiasih, Ni Luh Eka; Winaya, Ida Bagus Oka (Buletin Veteriner Udayana, 2018)
This study aims was to investigate the improvement of hepar histopathology experimental diabetic rats given moringa oleifera leaves ethanolic extract. 24 male white rats induced by a single dose STZ of 45mg/kg intraperitoneal to cause diabetes mellitus. After declared with diabetes disease, rats were divided into 6 groups consist of 1 a control group and a treatment group of 5 who were given ethanol extracts of leaves of the kelor, with a dose of 100, 200, 300, 400, and 500mg/kg, for 5 weeks. Rats then sacrificed and the hepar were taken for the histopathology preparations with Hematoxylin-Eosin staining (HE). Each preparation histopathology examined under a microscope in five visual fields at 400x magnification. The processed data is then analyzed statistically by test Non parametric Kruskal Wallis followed by Mann-Whitney test, when there is a significant difference (P<0.05). The results showed that the hepar has improved a result of the damage diabetes mellitus after given Moringa oleifera leaves ethanolic extract with a dose of 400 mg/kg.